CORIDS: a cluster‐oriented reward‐based intrusion detection system for wireless mesh networks. Issue 3 (12th March 2013) - Deb, Novarun; Chakraborty, Manali; Chaki, Nabendu
ABSTRACT Wireless mesh networks (WMNs) are proliferating as one of the key technologies of the next‐generation networks. Security is one of the prime concerns towards actual implementation of any network technology for commercial applications. Network security has intrinsically two approaches—prevention based and detection based. Implementing firewalls or intrusion prevention techniques is often not an attractive solution for energy‐constrained network nodes such as mobile ad hoc network (MANET) nodes or mesh clients in WMNs. However, in the era of pervasive and ubiquitous computing, commercial transactions are performed on the move and over portable devices such as cell phones and laptops. These devices have energy constraints, and hence, one cannot afford to adopt security measures with high computational overhead. This influences a shift in paradigm from active intrusion prevention to passive intrusion detection. In this paper, a new cluster‐oriented reward‐based intrusion detection system (CORIDS) has been proposed for WMNs. The performance of CORIDS has been evaluated using the Qualnet network simulator. Simulation results also establish superiority of CORIDS over Misbehavior Detection Algorithm, another recent trust‐based IDS for WMN, both in terms of higher detection efficiency and lower false positives. Copyright © 2013 John Wiley & Sons, Ltd.